COVID-19 pandemic: Impact on gestational diabetes mellitus prevalence. (January 2022) - Zanardo, Vincenzo; Tortora, Domenico; Sandri, Andrea; Severino, Lorenzo; Mesirca, Paolo; Straface, Gianluca
Highlights: An increased risk of gestational diabetes mellitus (GDM < ) has been reported in women exposed to stressful conditions. Limited information is available about such risk in the context of the COVID-19 pandemic. We found a significantly higher prevalence of GDM during the 2020 COVID-19 pandemic. Experiencing lockdown in the first trimester of gestation was a statistically significant contributing factor. Abstract: Aim: Although an increased risk of gestational diabetes mellitus (GDM) has been noted in women exposed to stressful conditions and traumatic events, limited information is available about such risk in the context of the COVID-19 pandemic. Methods: The study was designed as a non-concurrent case-control study on the prevalence of GDM, defined according to IADPSG 2010, in women giving birth during the COVID-19 pandemic in the hot spot of Northeast Italy from March 9th to May 18th, 2020, with an antecedent puerperae‐matched group whose women had given birth in 2019. Results: Analysis revealed that during the COVID-19 pandemic in 2020, GDM prevalence was significantly higher than in 2019 (GDM, 48/533, 9 vs 86/637, 13.5%, p = 0.01), as illustrated by a higher GDM prevalence in 5/6 months of the final semester of 2020. In addition, logistic regression analysis confirmed a statistically significant temporal relationship between experiencing the lockdown during the first trimester of gestation and later GDM incidence (t = 2.765, P = 0.012), with an 34% increase in mean number of GDM diagnoses per month (antilog of the parameter = 1.34). Conclusion: The COVID-19 pandemic negatively impacted GDM prevalence in 2020 compared to 2019, especially for pregnant women in the 1st trimester of gestation.